2021
DOI: 10.1088/1612-202x/19/1/015102
|View full text |Cite
|
Sign up to set email alerts
|

Er:fiber-based femtosecond frequency comb stabilized to an Yb+ single-ion optical frequency standard

Abstract: An erbium fiber-based femtosecond optical frequency comb stabilized to an Yb+ single-ion optical frequency standard was created. For the first time, a combination of an extra-cavity acousto-optic frequency modulator with fiber outputs and an intracavity electro-optic phase modulator based on a KTP crystal were used to stabilize offset frequency and one of the optical components of the Er:fiber femtosecond comb. As a result a locking bandwidth of 30 kHz for the optical comb offset frequency has been obtained. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…The frequency of each component is described by the formula: fN=f0+N*frep [2]. Due to the stabilisation of f0 and one component of the optical comb by an external optical reference standard, the intermode radio frequency frep of the FC is stabilised [3]. These systems are widely used for metrological tasks, including the positioning of terrestrial and space objects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of each component is described by the formula: fN=f0+N*frep [2]. Due to the stabilisation of f0 and one component of the optical comb by an external optical reference standard, the intermode radio frequency frep of the FC is stabilised [3]. These systems are widely used for metrological tasks, including the positioning of terrestrial and space objects.…”
mentioning
confidence: 99%
“…When operating the Er:fiber-based FC [3] in free regime during the working day, a change in the RF signal level f0 (10-15 dB) and in its frequency (20-30 MHz) was observed. This change in frequency and RF signal level of f0 negatively affects the operation of the FC phase lock systems in the full stabilisation regime.…”
mentioning
confidence: 99%
“…This standard has large dimensions (compared to the Nd:YAG/I2 standard), however, its predicted relative long-term instability reaches the level of ~10 -18 . It was shown that the fiber FC introduces into the output microwave frequencies a relative instability of no more than 5•10 −14 (for an averaging time of 1 s) and 2•10 −16 (for an averaging time of 400 s) in addition to the instability of the reference optical standard [7].…”
mentioning
confidence: 99%
“…Данный стандарт обладает большими габаритами (по сравнению с Nd:YAG/I2 стандартом), однако, его прогнозируемая относительная долговременная нестабильность достигает уровня ~10 -18 . При этом показано, что волоконный ФСЧ вносит в выходные СВЧ частоты относительную нестабильность не более 5•10 −14 (для времени усреднения 1 с) и 2•10 −16 (для времени усреднения 400 с) [7].…”
unclassified